EFEKTIVITAS PENGGUNAAN ARANG KAYU DAN BATOK KELAPA SEBAGAI PENGHAMBAT KERUSAKAN FISIK DAN KIMIA PADA DEDAK PADA SELAMA PROSES PENYIMPANAN 8 MINGGU - Basukoro, Satrio; Fathul, Farida; Sutrisna, Rudy (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2013)
Rice bran is a side product of the rice mill in producing rice. Rice bran is the part of rice husk thatis generated from the rice bleaching process. This feed is a material that would become fragile oreasily damage if it is kept beyond a certain time. The oil content that is relatively high makes ricebran not durable because oil is easily hydrolyzed so that make it rancid due lipase contained inrice. Prevention of feed damage during storage can be done by providing materials containingcertain active substances that can prevent damage. Charcoal gives a solution to prevent damageduring storage because of feed ingredients are hygroscopic and porous, which can absorb water upto the point of balance. The purpose of this study was to determine the effect of the use of woodcharcoal and coconut shell charcoal to physical and chemical damage of rice bran during 8 weeksperiod of storage. The experimental method that was used in this study is completely randomizeddesign CRD with 3 treatments and 4 replications. The use of coconut shell charcoal is better inmaintaining the rice bran odor, reducing the decrease of fat levels and minimizing the increase ofperoxide when compared to administration of charcoal wood.